Effectiveness of Decentralized Administration Management in Cambodia: A Comprehensive Review - Yin, Punleu; Serey, Mardy; Hour, Chhunkry; Chem, Vuthy (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
Decentralization has emerged as a key governance reform strategy aimed at improving administrative efficiency, enhancing citizen participation, and promoting equitable development. In Cambodia, decentralization reforms initiated in the early 2000s sought to transfer authority, financial resources, and decision-making powers from the central government to subnational levels, including provinces, municipalities, districts, and communes. This literature-based study evaluates the effectiveness of decentralized administration management in Cambodia, focusing on institutional capacity, service delivery performance, and governance outcomes. Drawing on case studies, comparative analyses with Indonesia, the Philippines, and Vietnam, and established theoretical frameworks such as New Public Management (NPM) and SERVQUAL, the review identifies both achievements and persistent challenges. Findings indicate that while decentralized administration in Cambodia has contributed to improved local governance and greater responsiveness to community needs, its effectiveness remains constrained by limited institutional capacity, infrastructural deficiencies, and the persistence of informal practices and corruption. The Kampong Speu Province case study illustrates how local governments have made progress in service accessibility and citizen engagement but continue to struggle with inefficiencies, uneven service quality, and weak accountability mechanisms. Comparative insights suggest that successful decentralization depends on robust institutional support, technological integration, and strong anti-corruption frameworks. This review concludes with policy recommendations aimed at strengthening human resource capacity, investing in digital infrastructure, enforcing transparency and accountability, and enhancing citizen participation in local governance. By addressing these areas, the Cambodian government can improve the functionality of decentralized administration and ensure more effective and inclusive public service delivery.